2012
DOI: 10.1007/s12149-012-0679-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of aortic 18F-FDG uptake and calcification in health-screening subjects

Abstract: Our data demonstrated the longitudinal progressions of vascular inflammation and calcification of health-screening subjects. Inflammation and calcification were observed to progress significantly faster in the abdominal aorta than in the thoracic aorta. The progressions of vascular inflammation and calcification may be associated with different atherogenic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Multiple regression analysis showed that progression of aortic calcifications was significantly associated with different atherogenic risk factors like age and smoking habit (P<0.001 and 0.0058 respectively) 24 .…”
Section: Discussionmentioning
confidence: 96%
“…Multiple regression analysis showed that progression of aortic calcifications was significantly associated with different atherogenic risk factors like age and smoking habit (P<0.001 and 0.0058 respectively) 24 .…”
Section: Discussionmentioning
confidence: 96%
“…There are structural and functional differences in the inherent biomechanical properties of the thoracic and abdominal aorta under normal conditions, as demonstrated by others (29,60). With cardiovascular disease and aging, there is also strong evidence to suggest that remodeling is also not uniform (47) and that the abdominal aorta is relatively stiffer compared with the more proximal regions of the aorta (20,22). Regional differences in the diseased aorta maybe due to differential changes in elastin and collagen content (53) and the subsequent impact on the mechanical properties (3).…”
mentioning
confidence: 88%
“…Tissue remodeling associated with cardiovascular disease and aging is not uniform along the length of the aorta 40 . The abdominal aorta is relatively stiffer than more proximal sites 41,42 .…”
Section: Resultsmentioning
confidence: 99%